(untitled) (Faridpur Medical College Journal, 2025)
Viral encephalitis, despite varying etiologies, often presents with similar clinical features, challenging clinicians in determining appropriate management strategies. This study aimed to investigate the etiological agents and associated clinical features of viral encephalitis in pediatric patients. A multicenter observational cross-sectional study was conducted over 15 months at the Department of Pediatric Neurology, Bangladesh Medical University (BMU), and the Department of Pediatrics, Dhaka Medical College Hospital. Sixty-four children with acute encephalitis were enrolled based on inclusion and exclusion criteria. Detailed clinical history, physical examination, and cerebrospinal fluid (CSF) analyses, including biochemical, cytological, bacteriological, and Neuro-9 viral panel studies, were performed. Informed consent was obtained from guardians. The mean age of participants was 4.10±3.87 years, with 59.4% aged ≤3 years. Varicella zoster virus (VZV) was the most frequently identified pathogen, present in 18.8% of cases, followed by Herpes Simplex Virus (HSV)-1 (3.1%) and Human Adenovirus (1.6%). No viral pathogen was identified in 76.5% of cases. Common presenting symptoms included fever (95.3%), seizures (87.5%), altered sensorium (85.9%), and prodromal symptoms (76.6%). In this cohort, the etiology of acute viral encephalitis remained unidentified in the majority of cases. VZV was the predominant virus detected, followed by HSV-1 and Adenovirus. Fever, seizures, altered sensorium, and prodromal symptoms were the most frequent clinical features. Thorough clinical evaluation is crucial for guiding management and excluding other differential diagnoses. Faridpur Med. Coll. J. 2025;20(2):07-12